Peningkatan Prestasi Belajar Pendidikan Agama Islam dengan di Iterapkan Metode Demontrasi Pada Siswa Kelas VIII di MTS Muhammad Basiuni Imran Sambas - Lusi; Rani; Tasya Ramadani; Putra, Purniadi (Jurnal Ilmu Sosial dan Humaniora, 2024)
Student success in learning is influenced by several factors, one of which is the method used by the teacher in teaching. In reality, in learning teacers use the classical method, namely lectures so that students are less active in learning and their learning achievement are less than satisfactory, therefore it is necessary to use other methods to improve learning achievements. The aim of This research is to determine the implementation of the demonstration learning method in improving student learning outcomes in each cycle in class VIII G MTS Muhammad Basiuni Imran Sambas through 4 stages, namely planning, observation, reflection, action, and observation. The subjects of this research were 27 students in class VIII G at  MTS Muhammad Basiuni Imran Sambas. The Hypothesis proposed is that if the demonstration method can be used  well, it can improve student learning achievement in PAI (FIQH) subjects in class VIII G MTS Muhammad Basiuni Imran Sambas. The Success indicator 77% with a KKM of 77, data collection techniques are observation, data analysis techniques with formulas to determine avarage values and  percentage